KONSENTRASI EMISI FORMALDEHIDA DAN ASETALDEHIDA DENGAN VARIASI AIR-FUEL RATIO DARI SEPEDA MOTOR DENGAN PENAMBAHAN BIOETANOL 10% PADA BAHAN BAKAR - Abimanyu Purwanto, Rakhmat
Motorcycle is a type of motor vehicle that many owned by Indonesia society. According to the Police Corps of the Republic of Indonesia, the number of motor vehicles operating in Indonesia in 2013 reaches 104,211 million units. Therefore, it is important to know the resulting gas emissions from motor vehicles. Formaldehyde and acetaldehyde is known as the main product of imperfect combustion of hydrocarbons. The aim of this study is to determine the concentration of formaldehyde and acetaldehyde as a result of bioethanol mixture fuel combustion (BE0 and BE10) on motorcycle which operating parameter, Air-Fuel Ratio (AFR), were varied. The use of bioethanol as a fuel will result in more complete combustion in motorcycle engine so that the exhaust gas cleaner. The concentration measurement of formaldehyde and acetaldehyde that generates from motorcycle emissions is carried out using Colorimetric MBTH method. The principle of this method is to drain the formaldehyde and acetaldehyde from motorcycle emissions through a system into an absorber containing MBTH (3-metil-2-benzothiazolinone hydrazone hydrochloride) solution. The concentration of formaldehyde and acetaldehyde then measured in the spectrophotometer with a wavelength of 630 nm. Based on the results of the study, it can be concluded that the largest emission factor of formaldehyde and acetaldehyde is owned by BE10 on all variations of the AFR. In addition, the size of the needle used is also one of the factors that affect the concentration of emissions produced by the motorcycle. The operation of motorcycle that varies depending on the variation value of the AFR will also affect the concentration of COx, NOx, and hydrocarbons. For both fuel, the richer the air contained in the combustion chamber, the better the emissions produced because the combustion is more perfect.